Evolution of Archaellum Rotation Involved Invention of a Stator Complex by Duplicating and Modifying a Core Component - Umrekar, Trishant R.; Winterborn, Yvonne B.; Sivabalasarma, Shamphavi; Brantl, Julian; Albers, Sonja-Verena; Beeby, Morgan (Frontiers in Microbiology, 2021)
Novelty in biology can arise from opportunistic repurposing of nascent characteristics of existing features. Understanding how this process happens at the molecular scale, however, suffers from a lack of case studies. The evolutionary emergence of rotary motors is a particularly clear example of evolution of a new function. The simplest of rotary motors is the archaellum, a molecular motor that spins a helical propeller for archaeal motility analogous to the bacterial flagellum. Curiously, emergence of archaellar rotation may have pivoted on the simple duplication and repurposing of a pre-existing component to produce a stator complex that anchors to the cell superstructure to enable productive rotation of the rotor component. This putative stator complex is composed of ArlF and ArlG, gene duplications of the filament component ArlB, providing an opportunity to study how gene duplication and neofunctionalization contributed to the radical innovation of rotary function. Toward understanding how this happened, we used electron cryomicroscopy to determine the structure of isolated ArlG filaments, the major component of the stator complex. Using a hybrid modeling approach incorporating structure prediction and validation, we show that ArlG filaments are open helices distinct to the closed helical filaments of ArlB. Curiously, further analysis reveals that ArlG retains a subset of the inter-protomer interactions of homologous ArlB, resulting in a superficially different assembly that nevertheless reflects the common ancestry of the two structures. This relatively simple mechanism to change quaternary structure was likely associated with the evolutionary neofunctionalization of the archaellar stator complex, and we speculate that the relative deformable elasticity of an open helix may facilitate elastic energy storage during the transmission of the discrete bursts of energy released by ATP hydrolysis to continuous archaellar rotation, allowing the inherent properties of a duplicated ArlB to be co-opted to fulfil a new role. Furthermore, agreement of diverse experimental evidence in our work supports recent claims to the power of new structure prediction techniques.